2019
DOI: 10.1029/2018ja025862
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Energy (<keV) O+ Ion Outflow Directly Into the Inner Magnetosphere: Van Allen Probes Observations

Abstract: The heavy ion component of the low‐energy (eV to hundreds of eV) ion population in the inner magnetosphere, also known as the O+ torus, is a crucial population for various aspects of magnetospheric dynamics. Yet even though its existence has been known since the 1980s, its formation remains an open question. We present a comprehensive study of a low‐energy ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 37 publications
8
69
2
Order By: Relevance
“…At <10 keV, whereas the PADs of all ion species have a strong field‐aligned anisotropy ( A ~−1.0), a mass‐dependent feature is seen in their normalized ion fluxes: heavier ions (He and O) show a strong enhancement in the field‐aligned direction during the dipolarization, unlike the H ions (Figure ). The field‐aligned low‐energy O ion enhancement is consistent with the Van Allen Probes observations of Nosé et al () and Gkioulidou et al (), who interpreted the low‐energy O ion enhancement in terms of the rapid outflow of O + ions from the topside ionosphere during the dipolarization event. Although neither papers examined the low‐energy He ions, it is possible that the field‐aligned low‐energy He ion enhancement occurs in a similar manner to the O ions (Hultqvist, ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…At <10 keV, whereas the PADs of all ion species have a strong field‐aligned anisotropy ( A ~−1.0), a mass‐dependent feature is seen in their normalized ion fluxes: heavier ions (He and O) show a strong enhancement in the field‐aligned direction during the dipolarization, unlike the H ions (Figure ). The field‐aligned low‐energy O ion enhancement is consistent with the Van Allen Probes observations of Nosé et al () and Gkioulidou et al (), who interpreted the low‐energy O ion enhancement in terms of the rapid outflow of O + ions from the topside ionosphere during the dipolarization event. Although neither papers examined the low‐energy He ions, it is possible that the field‐aligned low‐energy He ion enhancement occurs in a similar manner to the O ions (Hultqvist, ).…”
Section: Discussionsupporting
confidence: 88%
“…Whereas the lower energy He and O ion fluxes drop at α = 45–135° similar to the H ion flux, the He and O ion fluxes are enhanced only near the parallel and antiparallel directions. Such a field‐aligned enhancement of the lower energy O ions resembles that reported by Nosé et al () and Gkioulidou et al (), who suggested that the field‐aligned O ion flux enhancement likely arise from a prompt supply of ionospheric origin population O + into the inner magnetosphere after substorm onset. The travel time of 1–5 keV O + from the ionosphere to the inner magnetosphere ( r = 5–6 R E ) is approximately 2–5 min (cf.…”
Section: Superposed Epoch Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…The formulation can be gyroaveraged, for instance, for limiting the computational cost for electrons For instance, since the variation of the gyroradius among the particle species varies as 1∶40∶160 (e−:H+:O+), it is necessary to keep the gyrotrajectory when computing particle loss of heavy ions through the magnetopause (e.g., Sorathia et al, ). Global coupled MHD/test particle codes are well adapted, for instance, for azimuthal transport, that is, solving for particle gradient‐curvature drift motion, for rapid particle energization occurring during interplanetary shocks on the front end of coronal mass ejections (e.g., Hudson et al, ; Kress et al, , ), for drift‐orbit bifurcation trajectory (Ukhorskiy et al, ), for acceleration at dipolarization fronts (Ukhorskiy et al, in this collection), for solar wind ion entering the magnetosphere (Sorathia et al, ), for energetic particle injections in the inner magnetosphere during substorms (e.g., Gkioulidou et al, ), or O+ ion outflow directly injected within the radiation belts (Gkioulidou et al, ), or for the sudden depletion (e.g., Ukhorskiy et al, ) and rapid recovery of the outer belt (e.g., Sorathia et al, , in this collection). These codes can also be used to generate diffusion coefficients (e.g., Ukhorskiy & Sitnov, ).…”
Section: New Radiation Belt Modeling Capabilities and The Quantificatmentioning
confidence: 99%
“…In the inner magnetosphere DAWs have been observed coincident with O + outflow at energies reaching 10 keV (Chaston, Bonnell, Wygant, et al, ). Earthward directed Alfvénic Poynting fluxes have also been observed coincident with low‐energy (<1 keV) O + outflow deep in the inner magnetosphere (Gkioulidou et al, ). Recent simulations (Chaston et al, ) show that DAWs can continuously energize preexisting or outflowing O + trapped on closed magnetic field lines.…”
Section: Introductionmentioning
confidence: 99%